AVALIAÇÃO DO MÉTODO DE PRODAN NA AMOSTRAGEM DE CERRADO SENSU STRICTO NO DISTRITO FEDERAL - OLIVEIRA, Erica Karolina Barros de; COSTA, Lidiomar Soares da; LUSTOSA JUNIOR, Ilvan Medeiros; MURTA JÚNIOR, Leonidas Soares; BUCHMANN, Hugo Macedo; MOTA, Fabrícia Conceição Menez; REZENDE, Alba Valéria (Brazilian Journal of Biometrics, 2019)
This study aimed to evaluate and compare the sampling methods of Prodan and Fixed Area (plots) in Cerrado sensu stricto in the Distrito Federal, Brazil. For the Fixed Area method, 10 plots of 20 × 50 m were randomly distributed in the study area. In the center of each fixed area plot, points were marked for sampling by the Prodan method. In each sample unit, the trees were identified and the diameter at the base (Db ≥ 5 cm) and total height were measured. By Prodan method were sampled 39.1% of plant species and 60.7% of the botanical families that were sampled by the Fixed Area method. The plant species sampled by Prodan method were, mostly, those with higher relative values of frequency, density and dominance obtained in the Fixed Area method. The number of trees, basal area and volume per hectare did not differ between the two methods. Although the Prodan method obtain smaller samples in number of botanical species and families, it gets samples of the most representative species of phytosociology. The Prodan method is as efficient as the Fixed Area method for estimating tree numbers, basal area, and volume per hectare.